ANALISIS PENGARUH GOOD CORPORATE GOVERNANCE (GCG) DAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP PROFITABILITAS PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2020 - Lalu Rizal Ihwandi Lalu Rizal (Jurnal Akuntansi dan Keuangan Syariah - ALIANSI, 2023)
This study aims to determine the influence analysis of  Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) on the Profitability of banking companies listed on the Indonesia Stock Exchange. The population of this research is the banking industry as much as 46 and the research sample is 13 with the sampling technique using purposive sampling. Data analysis used multiple linear regression models and the research error rate was α = 5%. Based on the statistical results of the t-test with a t-value of -3.130. T table is searched at a significance of 0.05 the results are obtained for t table of 1,998 (-3,130> 1.998) with a significance level of 0.003 <0.05. Then Ho is rejected Ha is accepted so it can be concluded that Good Corporate Governance (GCG) has a significant effect on profitability. So is CSR on profitability. Based on the statistical results of the t-test with a t-value of -0.745. T table is searched at a significance of 0.05 the results are obtained for t table of 1,998 (-0.745 <1.998) with a significance level of 0.460 > 0.05. Then Ho is accepted  Ha is rejected so it can not be concluded that Corporate Social Responsibility (CSR) has a significant effect on profitability.   Keywords: Good Corporate Governance (GCG), Corporate Social Responsibility (CSR),   Profitability